Potensi Daur Ulang Sampah Domestik Di Wilayah Pengembangan III Kota Pekanbaru - Desra Shinta Hasri; Elvi Yenie; Muhammad Reza (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2021)
The purpose of this study was to determine the data on the potential for recycling of the domestic waste in the Development Region III of Pekanbaru City. Data obtained from research can be used for planning and developing waste management systems. Sampling is carried out based on SNI 193964-1994. The results showed that the potential for recycling waste by composting and recycling is 67.3% and the residue is 32.7% which can be managed in other ways. The waste is sorted and managed in other ways has its own economic value when sold. Of the 67 respondents from this study, the economic value achieved in a day is Rp. 155,835 or in a month Rp. 4,675,050. The waste is managed properly can be useful and have economic value and can reduce the accumulation of waste that causes environmental pollution. Keywords: potential for recycling waste.